2008
DOI: 10.1007/s11064-008-9736-3
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Optic Nerve Regeneration in Adult Mice with Pharmaceutical Approach

Abstract: Our previous research has suggested that lack of Bcl-2-supported axonal growth mechanisms and the presence of glial scarring following injury are major impediments of optic nerve regeneration in postnatal mice. Mice overexpressing Bcl-2 and simultaneously carrying impairment in glial scar formation supported robust optic nerve regeneration in the postnatal stage. To develop a therapeutic strategy for optic nerve damage, the combined effects of chemicals that induce Bcl-2 expression and selectively eliminate ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Lithium’s Bcl-2-dependent effects were later confirmed in vivo; in rats, lithium protects RGCs from partial optic nerve crush (Schuettauf et al, 2006). Co-application of lithium and astrotoxin, a glutamate analogue that selectively kills astrocytes with minimal effects on surrounding neurons, induces more robust optic nerve regeneration in adult mice (Cho & Chen, 2008). Lithium is also protective in cultured primary retinal neurocytes, where it promotes neurite outgrowth and DNA non-homologous end-joining following nutrient deprivation, an in vitro condition mimicking cell death in glaucoma (Zhuang et al, 2009).…”
Section: Lithium In Models Of Cns Disorders and Its Clinical Implimentioning
confidence: 99%
“…Lithium’s Bcl-2-dependent effects were later confirmed in vivo; in rats, lithium protects RGCs from partial optic nerve crush (Schuettauf et al, 2006). Co-application of lithium and astrotoxin, a glutamate analogue that selectively kills astrocytes with minimal effects on surrounding neurons, induces more robust optic nerve regeneration in adult mice (Cho & Chen, 2008). Lithium is also protective in cultured primary retinal neurocytes, where it promotes neurite outgrowth and DNA non-homologous end-joining following nutrient deprivation, an in vitro condition mimicking cell death in glaucoma (Zhuang et al, 2009).…”
Section: Lithium In Models Of Cns Disorders and Its Clinical Implimentioning
confidence: 99%
“…76 Lithium and other drugs have been treated as pharmaceutical approach to promote ON regeneration in animals. 77 To obtain further ON regeneration, those authors suggested to use lithium together with other drugs, citicoline, for instance, that mediate induction of permissive environment in the adult CNS.…”
Section: Lithiummentioning
confidence: 99%
“…BCL‐2 expression is turned off prenatally in the retinal neurons of mice, whereas BCL‐2 expression continues throughout life in fish and frogs and is upregulated during optic nerve regeneration (Chierzi et al, ). Several studies have shown that preventing reactive astrogliosis in the optic nerve and inducing the expression of Bcl‐2 results in the structural regeneration of the mouse optic nerve, including the re‐enervation of appropriate targets in the brain, although it was unclear whether vision was restored (Cho et al, ; Cho and Chen, ). The induction of BCL‐2 at P4 and the attenuation of reactive gliosis in mice result in rapid axonal regeneration over long distances.…”
Section: Mechanisms Of Astrocyte Activationmentioning
confidence: 99%